1989
DOI: 10.1148/radiology.171.1.2928532
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the cervix: staging with MR imaging.

Abstract: Demonstration and staging of carcinoma of the cervix with magnetic resonance (MR) imaging was evaluated prospectively in 67 patients with histologically proven lesions. Findings were correlated with surgical/pathologic results obtained within 2 weeks. MR imaging had an accuracy of 95% in demonstrating invasive disease (stage IB or higher). It was capable of depicting the location and extent of tumor invasion of cervical stroma and helped detect tumor beneath relatively normal epithelium or within the endocervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
2
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(104 citation statements)
references
References 0 publications
6
92
2
4
Order By: Relevance
“…21,22 Some reports have demonstrated the accuracy of MRI in the evaluation of the stage of cervical cancer ranged from 70% to 85%. [23][24][25] These results indicate higher accuracy rate of imaging modality than those of our study. However, a comparative study has reported the accuracy of CT and MRI to be 51% and 75%, respectively in the evaluation of cervical cancer.…”
Section: Discussioncontrasting
confidence: 41%
“…21,22 Some reports have demonstrated the accuracy of MRI in the evaluation of the stage of cervical cancer ranged from 70% to 85%. [23][24][25] These results indicate higher accuracy rate of imaging modality than those of our study. However, a comparative study has reported the accuracy of CT and MRI to be 51% and 75%, respectively in the evaluation of cervical cancer.…”
Section: Discussioncontrasting
confidence: 41%
“…We agreed with their description, and our draft also demonstrated this limitation. The accuracy of cervical mass measured only by MRI was superior to that measured by CT or MRI in previous study [1][2][3][4] as well as the reference which they described. 5 In the subgroup analysis which we have performed after publication, MRI was more accurate than CT for the evaluation of cervical mass in 25 patients who underwent both CT and MRI, even though small number and even without statistically significance (p=0.06).…”
Section: Modalities For Evaluation Of Tumor Size In Cervical Cancermentioning
confidence: 65%
“…4 However, the authors did not mention another study which included the re-analysis of the result of ACRIN 6651/GOG 183 Intergroup study and directly addressed the same issue with the current study. 4 In the study including 172 patients with cervical cancer, MRI is superior to CT and pelvic examination for measuring tumor size using pathologic results as the standard reference. 4 The authors should have explained the discrepancies between the current study and ACRIN 6651/GOG 183 Intergroup study.…”
Section: Modalities For Evaluation Of Tumor Size In Cervical Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…The utility of MR imaging in evaluating uterine cervical cancer before and after treatment has been established, [2][3][4][5] and the usefulness of contrast-enhanced dynamic MR imaging has been reported. [6][7][8] However, the use of gadolinium contrast agents has been associated with nephrogenic systemicˆbrosis (NSF), and their use in patients with advanced uterine cervical cancer carries the risk of hydronephrosis.…”
Section: Discussionmentioning
confidence: 99%